Pelaksanaan Asuhan Gizi Terstandar melalui Pemberian Diet Tinggi Kalori Tinggi Protein pada Pasien dengan Kejadian Dengue Fever (DF): Laporan Magang Kasus Dietetik Demam Berdarah (Studi di RS X Kota Sidoarjo) - Hasna Nur Sabrina; Qonita Rachmah; Yulia Adila (Universitas Airlangga, 2023)
Background: DF patients require special nutritional care to accelerate recovery and provide adequate nutritional intake. DF is an infectious condition due to dengue virus accompanied by prodromal symptoms of headache, pain in various parts of the body, anorexia, chills and malaise. Standardized nutritional care is carried out by providing a high-calorie and high-protein diet to meet the nutritional needs of patients, prevent damage to body tissues, normalize white blood cell levels due to infection and control body weight. Objectives: Knowing the implementation of standardized nutritional care processes and the provision of high-calorie, high-protein diets in DF patients. Methods: The case study was conducted in November 2021 on inpatients at RS X in Sidoarjo. Sampling of the study was carried out by selecting patients according to the criteria for large cases that had been previously determined by hospital nutritionists and internship supervisors. The research sample was taken by looking at the patient's medical record with the approval of the nurse on duty and accompanied by a hospital nutritionist. The method used was observation for 3 days on the aspect of intake seen from 8 meals of food recall 24H and visual comstock, physical aspects with interviews, and biochemical aspects seen from the patient's medical record. Researchers also conducted a literature study to complete the required data. Results: After nutritional intervention, the patient's physical condition began to improve, indicated by the appetite that had started to normal and complaints of nausea and vomiting that were no longer there. The patient's food intake which has started to improve from day to day is indicated by having reached the target (>70%). However, on the last day of the intervention the intake did not reach the target (<70%) because the patient had been allowed to go home by the doctor in charge. Conclusion: In this case, the recovery of the patient's condition was quite fast. The patient's digestive system began to improve marked by the disappearance of complaints of nausea and vomiting so that the patient's intake also improved.